Bleed for this [videorecording (DVD)] - Younger, Ben, 1972-; Teller, Miles; Eckhart, Aaron; Sagal, Katey (Universal Pictures Home Entertainment, 2017)
The inspirational story of world champion boxer Vinny Pazienza, who, after a near-fatal car crash, which left him not knowing if he'd ever walk again, made one of sports' most incredible comebacks.